CONSTRUCT VALIDATION FOR RESEARCH WITH DISTRIBUTORS OF A SUPPLY CHAIN WITH Q-SORT TECHNIQUE AND CONFIRMATORY FACTOR ANALYSIS - Redaelli, Emir José; Paiva, Ely Laureano; Teixeira, Rafael (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
Studies about supply china management are characterized by a great emphasis on the relationship between manufacturer and its supplies and few studies have focused on the relationship between manufacturer and its distributors. This study attempts to fulfill this gap in the literature by proposing the validation of theoretical constructs that contribute for future studies about the existent relationships in the downstream supply chain. More specifically, this study aims to construct and validate the following constructs: monitoring of distributor performance, direct involvement between manufacturer and distributor, resources and knowledge transfer, overall and operational performance of distributors. To do this, many steps were conducted to develop reliable and valid constructs. The questionnaire sorting technique as employed with twelve professors holding a Ph.D. as well as a confirmatory factor analysis was conducted with results obtained from 199 firms participating in the survey. The results led to improvement and validation of the measurement instrument.